IMPLEMENTASI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PENINGKATAN PROGRAM ADIWIYATA DI MTS AL-HIKAM JOMBANG - Nailul Marom; Abdullah Aminuddin Aziz (Jurnal Manajemen Pendidikan, 2026)
This research aims to explore in depth the implementation of Human Resource Development (HRD) in the enhancement of the Adiwiyata Program. The research was conducted at MTs Al-Hikam Jombang from November 2025 to April 2026. The research method employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation, accompanied by analysis and data validity testing. The results indicate that HRD at MTs Al-Hikam Jombang is implemented through training and development, organizational learning, leadership development, and knowledge management. These various forms of development successfully enhanced the knowledge, skills, abilities, competencies, and performance of the madrasah community in driving improvements to the Adiwiyata Program across policy, curriculum, instruction, activities, partnerships, facilities and infrastructure, and achievement of awards up to the Mandiri level, as well as the program’s sustainability at the international level through Al-Hikam Edu Tourism. In several cases, the success of the Adiwiyata program is largely determined by the quality of human resources. Previous studies have extensively examined HRD but have rarely linked it to this program or vice versa. Therefore, these factors emphasize the importance and novelty of this research.